2009
DOI: 10.1007/s00795-009-0453-z
|View full text |Cite
|
Sign up to set email alerts
|

Primitive neuroectodermal tumor of the kidney

Abstract: We report a 21-year-old man with a primitive neuroectodermal tumor (PNET) of the kidney that was difficult to distinguish from other small round cell tumors, e.g., small cell carcinoma, malignant lymphoma, and Wilms' tumor. Pathologically, a primitive rosette-like pattern was shown by H&E staining; expression of MIC-2 was indicated by an immunohistochemical test; rather primitive organelles were observed by an ultrastructural method; and translocation of chromosome 22 was confirmed by FISH. We therefore diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…pPNET of the kidney is an aggressive tumor with a poor prognosis; a previous study identified that 25–50% of patients presented with metastases and the five-year disease-free survival rate was ~45–55% ( 22 ). A review of 116 reported cases of renal pPNET demonstrated consistent results; 33% of patients exhibited metastases at diagnosis and 40% of patients developed metastases following surgery for the primary tumor ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…pPNET of the kidney is an aggressive tumor with a poor prognosis; a previous study identified that 25–50% of patients presented with metastases and the five-year disease-free survival rate was ~45–55% ( 22 ). A review of 116 reported cases of renal pPNET demonstrated consistent results; 33% of patients exhibited metastases at diagnosis and 40% of patients developed metastases following surgery for the primary tumor ( 8 ).…”
Section: Discussionmentioning
confidence: 99%